THE EFFECTIVENESS OF BASKETBALL SHOOTING TRAINING MODEL ON IMPROVING SHOOTING CAPABILITIES OF BASKETBALL PLAYERS IN PASURUAN REGENCY - Hendra Mashuri (Program Pascasarjana Universitas Negeri Jakarta, 2017)
AbstractShooting in a basketball game plays an important role in achieving the goal of the basketball game. Given that the basketball game tip is to insert the ball into the opponent's basket, therefore a good shooting technique is owned by every bolabasket player. Efforts to improve basketball shooting skills by using a basketball shooting practice model through a combination approach. The model combines shooting and physical engineering components supporting shooting techniques and using dill and games methods. The purpose of this research is to test the effectiveness of basket ball shooting practice model through combination approach. The research approach used is quantitative. This type of research is an experiment with randomized control group pre-test post-test design. The population of this study was a total of basketball players in Pasuruan District, the sample of this study amounted to 120 with 60 as the experimental group and 60 players as the control group. The data retrieval used is battery test shooting. Data analysis technique using t-test. The results showed that basketball shooting practice model through combination approach can improve basketball shooting ability with t-count value 33,262> t-table 2,00. So it can be concluded that the model of basketball shooting practice is effective against improving the shooting ability of basketball players.Keywords: Basketball Shooting, Combination Approach, Training Model.